The European Charter of Local Self-Government a treaty for local democracy - Himsworth, Chris (Edinburgh University Press, 2015)
Chris Himsworth analyses the text of the 1985 European Charter of Local Self-Government, traces its historical emergence and explains how it has been applied and interpreted throughout Europe, including the 2014 'Local and regional democracy in the United Kingdom' report published by the Council of Europe in March 2014